Маленькая принцесса: повесть / Фрэнсис Бёрнетт - Бернетт Френсис (Репро, 2020)
Экземпляры: БС (20210112) / Инвентарный номер: РТШ54986 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-4